The 3rd International Scientific Conference on Positive Management and Leadership in Socially Responsible Organisations - Lis, Andrzej (Journal of Corporate Responsibility and Leadership, 2019)
The 3rd International Scientific Conference on Positive Management and Leadership in Socially Responsible Organisations was conducted on 13 September 2018 at the Faculty of Economic Sciences and Management (FESM), Nicolaus Copernicus University (NCU) in Toruń. The aim of the conference was to establish the discussion platform for the researchers dealing with the aspects of positive management traditionally cultivated by the research community of the FESM NCU (cf. Stankiewicz (Ed.), 2010; Stankiewicz (Ed.), 2013). In 2018, similarly to previous editions of the conference (cf. Lis, 2016; Lis, 2017), the focus was given to the issues associated with: – “positive management including: interpersonal relationships, intra-organisational communication, trust, organisational citizenship behaviours; – leadership including: contemporary concepts of leadership, roles played by top, middle and first line managers, challenges (both external and intra-organisational) faced by leaders in business organisations, the public sector, and non-profit organisations; – corporate responsibility to employees and other stakeholders, organisations in business environment, society and the natural environment”.